"The future of in vitro toxicology". Issue 6 (September 2015) - Jennings, Paul
Highlights Toxicogenomics deeply impacted our understanding of chemical-induced cellular perturbations. iPSC allow us to address genetic diversity in populations. A tiered strategy could overcome the through-put limitations. An integrated interdisciplinary approach will be needed to realise an animal-free future.